Canonical Notch signaling is required for bone morphogenetic protein‐mediated human osteoblast differentiation. (24th June 2020) - Wagley, Yadav; Chesi, Alessandra; Acevedo, Parker K.; Lu, Sumei; Wells, Andrew D.; Johnson, Matthew E.; Grant, Struan F. A.; Hankenson, Kurt D.
Abstract: Osteoblast differentiation of bone marrow‐derived human mesenchymal stem cells (hMSC) can be induced by stimulation with canonical Notch ligand, Jagged1, or bone morphogenetic proteins (BMPs). However, it remains elusive how these two pathways lead to the same phenotypic outcome. Since Runx2 is regarded as a master regulator of osteoblastic differentiation, we targeted Runx2 with siRNA in hMSC. This abrogated both Jagged1 and BMP2 mediated osteoblastic differentiation, confirming the fundamental role for Runx2. However, while BMP stimulation increased Runx2 and downstream Osterix protein expression, Jagged1 treatment failed to upregulate either, suggesting that canonical Notch signals require basal Runx2 expression. To fully understand the transcriptomic profile of differentiating osteoblasts, RNA sequencing was performed in cells stimulated with BMP2 or Jagged1. There was common upregulation of ALPL and extracellular matrix genes, such as ACAN, HAS3, MCAM, and OLFML2B . Intriguingly, genes encoding components of Notch signaling ( JAG1, HEY2, and HES4 ) were among the top 10 genes upregulated by both stimuli. Indeed, ALPL expression occurred concurrently with Notch activation and inhibiting Notch activity for up to 24 hours after BMP administration with DAPT (a gamma secretase inhibitor) completely abrogated hMSC osteoblastogenesis. Concordantly, RBPJ (recombination signal binding protein for immunoglobulin kappa J region, a critical downstream modulator of Notch signals) binding could be demonstrated within the ALPL and SP7 promoters. As such, siRNA‐mediated ablation of RBPJ decreased BMP‐mediated osteoblastogenesis. Finally, systemic Notch inhibition using diabenzazepine (DBZ) reduced BMP2‐induced calvarial bone healing in mice supporting the critical regulatory role of Notch signaling in BMP‐induced osteoblastogenesis . Abstract : Bone morphogenetic protein (BMP) stimulation of bone‐marrow‐derived human mesenchymal progenitor cells (hMSCs) increases Notch proteins via increased Notch ligand Jagged1 expression. Canonical Notch signaling is required for BMP‐induced ALPL expression and osteoblastic commitment of hMSCs. Both BMP‐induced osteoblastogenesis and Notch‐induced osteoblastogenesis require Runx2.